A Musical Education: Lee Morgan and the Philadelphia Jazz Scene of the 1950s - McMillan, Jeffrey S. (Current Musicology, 2001)
When Michael LaVoe observed Lee Morgan, a fellow freshman at Philadelphia’s Mastbaum Vocational Technical High School, playing trumpet with members of the school’s dance band in the first days of school in September 1953, he could not believe his ears. Morgan, who had just turned fifteen years old the previous July, had remarkable facility on his instrument and displayed a sophisticated understanding of music for someone so young. Other members of the ensemble, some of whom al-ready had three years of musical training and performing experience in the school’s vocational music program, experienced similar feelings of dis-belief when they heard the newcomer’s precocious ability. Lee Morgan had successfully auditioned into Mastbaum’s music program, the strongest of its kind in Philadelphia from the 1930s through the 1960s, and demon-strated a rare ability that begged the title "prodigy."